Whole‐brain microstructural white matter alterations in borderline personality disorder patients. (16th April 2019) - Quattrini, Giulia; Marizzoni, Moira; Magni, Laura R.; Magnaldi, Silvia; Lanfredi, Mariangela; Rossi, Giuseppe; Frisoni, Giovanni B.; Pievani, Michela; Rossi, Roberta
Abstract: Background: Borderline personality disorder (BPD) is a psychiatric condition associated with the impairment of the frontolimbic network. However, a growing body of studies suggests that brain dysfunction underling BPD could involve other brain areas. We explored the whole‐brain white matter (WM) organization in BPD patients to clarify the structural pattern underlying the disease and its relationship with clinical features. Methods: Fourteen BPD patients and 14 healthy controls underwent a multidimensional clinical assessment and diffusion tensor imaging acquisition. Measures of fractional anisotropy (FA) and mean, axial and radial (RD) diffusivity were collected, and alterations in the WM were assessed using the voxelwise approach, including substance and alcohol abuse as covariates. Voxelwise regression analysis was performed to identify associations between microstructural changes and clinical feature in BPD. Results: Group comparisons showed alterations only for FA and RD: FA decreased in the right posterior hemisphere, while RD increased bilaterally and widespread in anterior and posterior areas ( p < 0.05, threshold‐free cluster enhancement corrected). Moreover, WM alterations of the corpus callosum were related to anxiety in BPD group. Discussion: Our data support the idea that structural alterations underling BPD also involve cortico‐cortical pathways, corticothalamic and corticostriatal tracts, suggesting that the frontolimbic model should be reinterpreted. © 2019 John Wiley & Sons, Ltd.